Effect of Sleep Quality on Cognitive and Physiological Functions among Patients Admitted in Medical Wards - Gracy Philip, Persis; Ponchitra, R. (International Journal of Nursing Research, 2023)
Introduction: Sleep is crucial for the survival of a human being as food. It helps to increase physiological and cognitive functions. Sleep is defined as transformable condition, where there is a withdrawal from the extrinsic environment. Sleep permits to rejuvenate the physical and physiological function. Disrupted sleep also leads to brain dysfunction and hemodynamic alterations. Materials and Methods: A quasi-experimental study was considered to attain the objectives of the study. On probability, convenient sampling was done. The pre-interventional data were collected on day 0. Eye mask and ear plug were given as intervention from day 1 to day 3.and data were collected on each day. Results: The study was conducted on 60 samples. The study reveals that majority of patients were between 40 and 59 years and out of 60 patients, majority of the patients were female It was found that the patients average sleeping hours at home were 6–9 h and patients had no difficulty in initiating sleep in normal routine sleep. Patients had deprived sleep due to continuous light and sound. The sleep status is improved from day 1 to day 3. There was significant relationship between the heart rate, blood pressure, respiration, and sleep quality; there was no significant relationship between cognitive function and sleep. Conclusion: The present study reveals that the sleep quality was enhanced by the application of eye mask and ear plug which led to changes in the physiological parameters such as blood pressure and heart rate. The blood pressure came down to normal limit with sleep quality